2020
DOI: 10.1038/s41467-020-17099-3
|View full text |Cite
|
Sign up to set email alerts
|

A FAK/HDAC5 signaling axis controls osteocyte mechanotransduction

Abstract: Osteocytes, cells ensconced within mineralized bone matrix, are the primary skeletal mechanosensors. Osteocytes sense mechanical cues by changes in fluid flow shear stress (FFSS) across their dendritic projections. Loading-induced reductions of osteocytic Sclerostin (encoded by Sost) expression stimulates new bone formation. However, the molecular steps linking mechanotransduction and Sost suppression remain unknown. Here, we report that class IIa histone deacetylases (HDAC4 and HDAC5) are required for loading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
58
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 104 publications
(118 reference statements)
2
58
0
Order By: Relevance
“…The importance for Kindlin-2 in osteocyte mechanotransduction could be related to its functions in FA. Previous studies showed that FA proteins are essential for bone mass maintenance in mechanical stimulation, such as integrin-β1 81 83 , FAK 84 , and Pinch1/2 85 , 86 . Our results demonstrate that Kindlin-2 controls osteocyte FA formation, cell spreading, cell attachment, and cell morphology both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…The importance for Kindlin-2 in osteocyte mechanotransduction could be related to its functions in FA. Previous studies showed that FA proteins are essential for bone mass maintenance in mechanical stimulation, such as integrin-β1 81 83 , FAK 84 , and Pinch1/2 85 , 86 . Our results demonstrate that Kindlin-2 controls osteocyte FA formation, cell spreading, cell attachment, and cell morphology both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Immunoblotting and ELISA Immunoblotting was performed as previously described [69,70]. For both Ocy454 and MC3T3-E1 Sp7 knockdown and overexpressing cells, whole cell lysates were prepared using TNT (Tris-NaCl-Tween buffer, 20 mM Tris-HCl pH = 8, mM NaCl, 0.5% Triton X-100 containing protease inhibitor (PI), 1 mM NaF, 1 mM DTT, 1 mM vanadate).…”
Section: Ocy454mentioning
confidence: 99%
“…These data do not preclude a transcriptional control of the Sost gene by osteoanabolic stimuli ( Tu et al, 2012 ; Sato et al, 2020 ). Rather, they add an important downstream check point for regulating sclerostin protein bioavailability with remarkable temporal control.…”
Section: Discussionmentioning
confidence: 70%
“…Finally, we link sclerostin degradation not only to skeletal physiology in mice but also to human disease using Gaucher disease iPSCs. These data do not preclude a transcriptional control of the Sost gene by osteoanabolic stimuli (47,48). Rather, they add an important downstream check point for regulating sclerostin protein bioavailability with remarkable temporal control.…”
Section: Discussionmentioning
confidence: 85%